Infovigilância e controle: violência invisível na cibercultura - Silva, Mario Finotti (2018)
The purpose of this Doctoral Thesis is to investigate surveillance and control within the cyberculture and to observe the modus operandi that – through the using of electronic equipment – has settled the invisible violence that silently watches over society and – at the same time – is accepted by many as a necessity of our time. Currently, the technological wonder determined by the technology giants through hardware, software and the speech of bringing people together, puts the user in the basic condition of use, since, this way, there is a guarantee of freedom. The reality is opposite though. The more freedom of choice, the more technological control. Through this slant, a violence that goes unnoticed by all operates. The technological progress – allied with innovation – has enabled mankind to be able to adapt to the new features embedded in electronic gadgets; tools that are always at hand. The urgency in learning is a crucial factor for permanence in this territory of continuous updating. Users who are not able to keep pace with this progress tend to stay at the marginality and, consequently, to be excluded. Companies – aware of this condition – hurry to release products with novelty features that will probably never be used. Not because of them, but because this modality allows them to settle and to deposit all the wounds of life in devices that can determine and guarantee their future. It also allows them to give up their natural state and to understand the benefit of the devices, such as security, even if being monitored twenty-four hours a day. What is the limit of this proposal for autonomy, which, while offering choices, can bump into the freedom once much before promoted by an array of thinkers? Since there is more security and justice ensured, the rate of freedom lowers. The fascination promoted and the progress stipulated / manipulated by the big corporations impose the feeling of protection as a preponderant factor for the existence and the maintenance of the sedation of the people. In a world troubled by speculations of surveillance, power and control, this research is focused on authors that justify its reading and that lead to a more in-depth reflection on the proposed theme. Some of them, more relevant, significantly contribute to this given Thesis: Virilio (1996), Bauman (2013), Rüdiger (2002), Lyon (1994) and Trivinho (2007), all of which have sought to study the impact of the digital technologies on social life. On another vertent are: Castells (1999), Bourdieu (2012), Deleuze (1992) and Foucault (1987), which analyze the condition of surveillance and control, from the social to the technological point of view. Wiener (1978) verifies its unfolding in a society marked by cybernetics. Other authors, equally important, such as Toynbee (1971), already verified in the 1970s the technological power on the hands of the companies. In contemporaneity, authors like Postman (1994) and Assange (2013) observe that the technological condition is favorable towards the one who holds the power, given that the rules are not egalitarian. In view of that, we conclude that while ordinary users require privacy, governments and corporations violate this condition to be able to exercise control closely. However, for the microsphere of power, information must be crystal clear with the purpose of maintaining and supporting surveillance on the bodies of living beings